Laryngeal mask airway in prone position in ambulatory surgery: a prospective observational study - Araújo, Marta (2015)
Introduction: The laryngeal mask airway (LMA) is a common airway device used for anesthesia in ambulatory surgery, with a recently new described utilization in prone position. The aim of this study was to evaluate the safety and the effectiveness of the LMA, in prone position for anesthesia in ambulatory surgery, based on our new anesthesia department protocol. Methods: Patients from February 2013 to July 2014 were included in this prospective study. After the patient selfpositioning in prone position, general anesthesia was induced and the LMA was placed. Second generation LMA types were used (Supreme™, iGel™ and Proseal™) and all patients were mechanically ventilated. At the end of surgery, LMA was removed in prone or supine position. Number of attempts of LMA insertion, volume leak, airway peak pressure and complications were registered until 2 hours after the procedure. Results: The LMA placement was 85.1% effective in the first attempt and 100% in the second attempt. The need for a second attempt LMA placement was due to non-progression of the aspiration probe, a high leak and impossible ventilation. Mechanical ventilation was considered effective and safe with maximum peak airway pressure of 17.9 ± 5.5 cm H2O and maximum leak of 47.7 ± 31.2 ml. Complications were present in 6 patients (9%) with hypoventilation, bronchospasm and laryngospasm. Other “minor” events registered included the presence of blood in the LMA at the end of procedure and gum lesion with the rigid piece of the Supreme™ LMA. Discussion and conclusion: Complications found in our study are similar to those described in literature in supine position and are related to the anesthetist previous experience. Anesthetic depth adjustment improved all complications found. Effectiveness and overall safety of LMA use in prone position was observed, allowing further utilizations in selected patients according to the anesthesia department protocol.